KESULITAN BELAJAR BERLATAR INTERAKSI SOSIAL PESERTA DIDIK DI SEKOLAH - Herawati Herawati (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2018)
Learning difficulty is a barrier in a learning process which is faced by students so he/she cannot achieve academical achievement that he/she wants, Meanwhile social interaction is a mutual relationship process or interaction between 2 or more individuals which affect each other as individual developmental step in social situation in anywhere they live. This study was conducted to obtain how much the frequency distribution of learning difficulties and social interaction and also the students individual description who have learning difficulties and social interaction problems. Participants amounted to 217 students of 11th graders in SMA Negeri 15 Bandung. The research method used for data collection is descriptive analysis. The instrument used is a closed questionnaire using the Guttman scale with a choice of Yes or No answers. The results of this study revealed that learning difficulties students 11th graders in SMAN 15 Bandung are in the low category. Meanwhile their level of social interaction is high category. Six students are also found having both learning and social interaction difficulties with different symptoms.